The known-unknowns in spinal cord injury, with emphasis on cell-based therapies – a review with suggestive arenas for research. (May 2014) - Dedeepiya, Vidyasagar Devaprasad; William, Justin Benjamin; Parthiban, Jutty KBC; Chidambaram, Ranganathan; Balamurugan, Madasamy; Kuroda, Satoshi; Iwasaki, Masaru; Preethy, Senthilkumar; Abraham, Samuel JK
<x xml:space="preserve">Abstract</x> Introduction: In spite of extensive research, the progress toward a cure in spinal cord injury (SCI) is still elusive, which holds good for the cell- and stem cell-based therapies. We have critically analyzed seven known gray areas in SCI, indicating the specific arenas for research to improvise the outcome of cell-based therapies in SCI. Areas covered: The seven, specific known gray areas in SCI analyzed are: i) the gap between animal models and human victims; ii) uncertainty about the time, route and dosage of cells applied; iii) source of the most efficacious cells for therapy; iv) inability to address the vascular compromise during SCI; v) lack of non-invasive methodologies to track the transplanted cells; vi) need for scaffolds to retain the cells at the site of injury; and vii) physical and chemical stimuli that might be required for synapses formation yielding functional neurons. Expert opinion: Further research on scaffolds for retaining the transplanted cells at the lesion, chemical and physical stimuli that may help neurons become functional, a meta-analysis of timing of the cell therapy, mode of application and larger clinical studies are essential to improve the outcome.